The relevance of surveying content in mining engineering education. - O.P. Oshokoya; S. Naidoo (CONSAS Conference, 2014)
The University of the Witwatersrand School of Mining Engineering (Wits Mining) has its origins in the South African School of Mines, which was established in 1896. It is currently recognised as one of the world’s top mining engineering schools that educate mining engineering candidates to become qualified to specialise in a variety of disciplines required in a modern mining environment. At undergraduate level, Wits mining offers one degree programme – B.Sc. in mining engineering. The role of Wits Mining has been one of successfully facilitating the continuous professional development of mining engineers and mining specialists like mine surveyors. The paper will highlight the surveying content that is relevant to the mining engineering programme according to the Engineering Council of South Africa (ECSA) by show-casing the surveying content within the Wits Mining programme and comparing this with what is obtainable at other international schools of mining engineering, such as Aachen University (Germany), the University of Mines and Technology (Ghana) and the University of Johannesburg (South Africa). The training of mine surveyors is well established in South Africa, and Wits University is an institution where a mine surveyor can obtain a Master’s degree specialising in any one of 5 mining specialisations, including Mine Surveying. This article attempts to answer the question as to what mining engineers should know about mine surveying. The paper will also explain how mine surveying training is beneficial to a mining engineer’s career development.
Keywords: Education; Specialisation; Degree programme; Wits mining; Surveying; Mine surveyors; University of the Witwatersrand; Research Subject Categories::TECHNOLOGY